Recent developments in electronics and communication systems proceedings of the first International Conference on Recent Developments in Electronics and Communication Systems (RDECS-2022) - Ramachandra Murthy, K. V. S.; Kumar, Sanjeev; Singh, Mahesh Kumar (IOS Press, 2023)
Intro -- Title Page -- Preface -- About the Conference -- Contents -- RESMOTE: A New Approach for Class Imbalance Problem -- Query Recommendation for Search Engine Results Using Machine Learning -- Web Defenselessness Recognition Against Case of Cross Site Demand Fake -- Modelling and Controlling a Buck Converter Using Shunt Active Power Filter -- Quantum Computing in Image Processing -- Research into Wind Speeds and Energy Generation in India: An Overview -- Role of IoT to Avoid Spreading of Covid19 -- Comparative Analysis of Approximate Integer and Floating-Point Multiplier -- IoT Application for Home Automation -- Designing a Strong Physically Unclonable Function Using Low Power LFSR -- Health Information Sharing in Cloud Environment Using Modular Encryption Standard -- Stochastic Computing Solutions Challenges and Application -- A New Model That Figures out Sub-Emotionality and the Changes in It over Time -- Interference-Normalized Least Mean Square Algorithm: A Comparative Study -- Image Classification of Land Use Land Cover of Bengaluru City Using Convolutional Neural Network -- The Journey of Logarithm Multiplier: Approach, Development and Future Scope -- Analysis of Kinematics of a 12-DOF Biped Robot Gait by Parametrization of Its Body Trajectories -- Bibliometric Analysis on Identifying Plant, Crop Diseases Using Machine Learning and Deep Learning -- A Study on Emergent Augmented Intelligence Applications in Structural Engineering -- Logarithm and Antilogarithm Converter with Accurate Error Correction -- Voice-Based E-Mail System for Visually Challenged People -- Performance Evaluation of IoT in 5G Technologies for Fire and Spark Activity Detection -- A Novel Hybrid GWO-FA to Locate Unknown Node in 2D Environment -- A Review on Intelligent Health Care System Using Learning Methods.
Open access
Keywords: Electronic books; Konferenzschrift